180k views
5 votes
Let f(x) = -3x - 4 and g(x) = 2x - 6. Find (f * g)(1)

2 Answers

5 votes

Answer:
(f*g)(1)=28

Explanation:

To solve the exercise you need to apply the proccedure shown below:

- You must multiply the functions given in the problem. Then:


(f*g)(x)=(-3x - 4)(2x-6)\\(f*g)(x)=-6x^2+18x-8x+24\\(f*g)(x)=-6x^2+10x+24

- Now, you must susbtitute x=1 into (f*g)(x), and simplify the function, as you can see below. Therefore, you obtain:


(f*g)(1)=-6(1)^2+10(1)+24\\(f*g)(1)=-6+10+24\\(f*g)(1)=28

User Mjimcua
by
5.7k points
3 votes

Answer:

28

Explanation:

Given two functions

f(x) = -3x - 4

g(x) = 2x - 6

To find

(f * g)(1)

First we need to find (f * g)

(-3x-4)(2x-6)

-3x(2x) + (-3x)(-6) + -4(2x) + -4(-6)

-6x² + 18x - 8x + 24

-6x² + 10x + 24

Now plug x = 1

-6(1)² + 10(1) + 24

-6 + 10 + 24

28

So, (f * g)(1) = 28

User Iqbalzas
by
5.6k points